88.4k views
0 votes
-5x + (-2) = -2x + 4​

User Stacee
by
5.4k points

2 Answers

3 votes

Answer:

(-2, 0)

Explanation:

Standard form:

−3x − 6 = 0

Factorization:

−3(x + 2) = 0

Solutions:

x = −6 /3 = −2

x=-2

y=0

User Kiwikodes
by
5.1k points
3 votes

Answer:

x=-2

Explanation:

-5x-2=-2x+4

+2 +2

__________________-

-5x=-2x+6

+2x +2x

_______________-

-3x=6

÷-3 ÷-3

___________________

x=-2

Hope this helps ∞<3

User Neto Braghetto
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.